TEPUNG SUSU KAMBING, TEPUNG KACANG KEDELAI, GULA SORGHUM, TEPUNG RUMPUT LAUT COKLAT SEBAGAI FORMULA ENTERAL BAGI PASIEN PENYAKIT HATI KRONIS - Sulaeman, Agus; Azhari, Swary Anistri (Jurnal Inovasi Bahan Lokal dan Pemberdayaan Masyarakat, 2024)
The World Health Organization (WHO) in 2021 shows that 1% or 71 million people worldwide are infected with the hepatitis C virus (HCV). Riset Kesehatan Dasar (Riskesdas) in 2018, the highest prevalence of hepatitis was in Papua province (0.66%) and West Java Province had a prevalence of (0.4%). Malnutrition problems often arise in patients with liver disorders. The main causes of malnutrition are multifactorial, such as loss of appetite and inadequate oral intake, malabsorption and increased nutritional requirements. Intervention in the form of enteral formula can be an alternative, generally given in commercial enteral form, which is relatively expensive. Hospital Enteral Formulas are starting to be developed but the shelf life is relatively short due to the liquid ingredients. The aim of this research was to determine the effect of Etawa goat's milk flour and soybean flour formulations on organoleptic, viscosity, flowability and price. The research design was experimental and the sample for organoleptic testing was 30 somewhat trained panelists. The results of research on the organoleptic properties of the three formulas concluded that there were significant differences p (0.035) < α (0.05) in taste, p (0.006) < α (0.05) in color and no significant differences in flavor, consistency and overall as well as flowability and viscosity with p > 0.05. F1 is the best formula that the panelists like. Keywords: Enteral Formula, Chronic Liver Disease Patients, Etawa Goat Milk Flour, Soybean Flour, Brown Seaweed Flour, Sorghum Sugar